Addressing the impacts of climate emergency and building resilence in post-war northern Province, Sri Lanka. - Sujeevan, T.; Nivetha, S.; Karthiga, U.; Rakulan, N.; Navaprasanth, R.; Stalini, M.; Sankavi, K.; Shribavan, K.; Suren, S.N.; Prabu (University of Jaffna, 2020)
Sri Lanka ranks second among the ten countries most affected by extreme weather events recorded since 1998 according to the Climate Risk Index 2019. The Northern and Eastern provinces are among the most vulnerable to impacts of climate change. The post-war boom in auto sales, industrialization of agriculture and unprecedented infrastructure development add further to the effects of climate change. One climate action that links innovation, communication, entrepreneurship, and community participation is Climathon. Targeting youth, it features local level ideathons where cities and citizens co-create ideas for climate challenges. A local movement named Organic Movement of North and East along with other youth volunteer organisations(Eleven organisations), successfully staged the Climathon event for the first time in Sri Lanka in 2019 and again in 2020 to engage local entrepreneurs, environmental working groups, policy makers and the public in addressing the local climate challenges and building resilience. Climathon involved three groups of actors – organisers which included judges, mentors and coaches; participants and the wider Jaffna community including City administration. The event had four orientations – reform of the existing food and water system, developing a sustainable waste management system, concept of sustainable city development, and broad climate change awareness and action. Leaflets, YouTube, Facebook, newspapers, and discussions in local TV were used to communicate the theme and the event to the wider community. While the global focus of Climathon was novel local solutions via the ideathon component, Climathon Jaffna deployed a range of events and activities to ensure effective community mobilisation. Coaching workshops, ideation sessions, group discussions, keynote speeches, photography and drawing exhibits, action theatre and debate were all employed to communicate sustainability aspects among participants and organizers.